THE NEED OF THE BALANCE OF RISKS AND PROTECTION OF STAKEHOLDERS INTERESTS IN STRATEGIC MANAGEMENT OF FINANCIAL AND ECONOMIC SECURITY OF BUSINESS ENTITIES - Z. B. Zhyvko; O. V. Cherevko; N. V. Zachosova; O. M. Balynska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The necessity of balancing the processes of ensuring the maximum level of satisfaction of interests of stakeholders of business entities and risk management during the realization of the tasks of strategic management of financial and economic security is substantiated. The definition of strategic management of financial and economic security is proposed, according to which its concept is interpreted as a process of using the entrepreneurial capabilities of a business entity to ensure the stability of its operation and to achieve long-term goals in the conditions of the constant need to protect corporate resources from the negative impact of external and internal threats and risks. The role of the stakeholders interests have been established in the processes of strategic management, risk management and financial and economic security management. The interests of stakeholders of business entities and the risks to financial and economic security that arise during their satisfaction are critically assessed and summarized. According to the results of the questionnaire of experts — representatives of business owners and top managers of a number of companies that carry out financial and business activities in the Ukrainian market, quantitative indicators of managers that would decide on the adoption of economic risk to meet the interests of stakeholders in the strategic perspective were made. A map of stakeholders of business entities for the needs of strategic management of financial and economic security of business structures is offered. It is proposed to initiate the process of forming risk catalogs taking into account the probability of their occurrence, depending on the level of stakeholders interests and needs satisfaction. The necessity of combining mechanisms of stakeholder management, strategic management, risk management and financial and economic security management in the integrated system of security-oriented management of economic entities in the conditions of financial instability characteristic of the post-crisis period of recovery and development of the Ukrainian economy is proved.